In Vitro Susceptibility Profiles of Klebsiella spp. Isolated from ICU and non-ICU Wards in North and Latin America (TEST Program 2012–2016). (4th October 2017) - Hoban, Daryl; Renteria, Martha; Sahm, Dan; Leister-Tebbe, Heidi
Abstract: Background: Klebsiella spp. are one of the most frequently isolated Gram-negative pathogens infecting seriously ill patients in intensive care units. Increasing resistance mechanisms associated with this species group has led to the inclusion of K. pneumoniae as a member of the ESKAPE pathogens as determined by the Infectious Disease Society of America (IDSA). Regional variations of susceptibility to several classes of antimicrobial agents can provide guidance when selecting appropriate antimicrobial therapy. Data from Tigecycline Evaluation Surveillance Trial (TEST) program 2012-2016 were used to determine antimicrobial susceptibility patterns in Klebsiella spp.in patients in ICUs and non-ICUs in both Latin America (LA) and North America (NA). Methods: Klebsiella spp. isolates were identified locally and antimicrobial susceptibility testing was done using broth microdilution according to CLSI guidelines at each participating institution in NA and LA. CLSI or FDA (tigecycline) breakpoint criteria were applied to define susceptibility status. Results: Susceptibility by region and patient location are shown in the following table. Conclusion: Klebsiella spp. infections are becoming a treatment challenge due to several resistance mechanisms, particularly β-lactamases. Decreased activities among all agents were observed among Klebsiella spp. isolates collected in LA compared with NA. Isolates of Klebsiella spp. collected from patients in ICU wards demonstrated comparable susceptibility to those from non-ICU wards in both North America and Latin America. Because resistance patterns can vary with patient locations continued monitoring of antimicrobial trends based on location parameters is warranted. Disclosures: M. Renteria, IHMA, Inc.: Employee, Salary. H. Leister-Tebbe, Pfizer: Employee, Salary